Oxford Reading Tree Playscripts - A Day In London - Roderick Hunt (Bharat Oxford Reading, 1998)
The Stage 8 Biff, Chip and Kipper stories provide a rich story context to help develop language comprehension and decoding skills. Stories and More Stories continue to provide a mix of fantasy settings and familiar situations. More complex sentences develop stamina, to enable readers to progress with confidence.
Keywords: Play/Drama -- Read Aloud